Micropropagation of nucellar embryos and their histological comparative study for regeneration ability with other explants of kinnow mandarin (Citrus reticulata blanco) - Kazmi, Syeda Kahkashan; Khan, Saifullah; Mirbahar, Ameer Ahmed; Kabir, Nurul (Pakistan Botanical Society, 2018)
Polyembryony is the most beneficial and distinct character in citrus seeds. This characteristic can be beneficial in citrus improvement programs. Nucellar embryos developed from nucellar wall in citrus seeds along with zygotic embryo are found to have high plants regeneration ability in comparison to zygotic embryos. Under In vitro culture conditions, nucellar embryos were detected and multiplied on MT media with 0.5ml of coconut water along with 50g/L sucrose. These nucellar embryonic tissues were also regenerated on MT media supplemented with 0.5 mg/L BAP and 0.5 mg/L kinetin. Many shoots were regenerated from nucellar embryonic tissue; these shoots were rooted on MT media supplemented with IBA 0.5mg/L and NAA 0.1 mg/L in addition to activated charcoal 0.5gm/L. The resulting plantlets were acclimatized in the green house. After micropropagation, histological studies of nucellar embryonic tissues were carried out under fluorescence microscope to examine their high regeneration ability in comparison with usual plant parts, like seeds, shoots as well as with tissue culture stages including embryogenic and non-embryogenic callus. It was found that nucellar embryos have more regeneration ability as compared to usual plant parts and other tissue culture stages.